Implementation of Research Results in Preparing a Housing Planning Textbook - Sri Suryani Yuprapti Winarsih; Muchlisiniyati Safeyah; Lily Syahrial (Nusantara Science and Technology Proceedings)
Learning is an activity undertaken by students to achieve educational goals. This learning process takes place in the interaction between the components of students (students) and educators (lecturers) with the content of educational goals. While learning outcomes can be classified into three, 1) effectiveness, which is measured by the level of student achievement, 2). Efficient, measured by the ratio between effectiveness and the amount of study time and/or the number of learning costs, 3). Attractiveness, which is measured by observing the tendency of students to keep learning. Housing planning is one of the courses taught in UPNVJT Architecture education that studies the elements, guidelines, and provisions involved in planning a residential environment. This Textbook is the result of previous research entitled "The Concept of Open Space Planning in simple housing based on community participation", and "Regional Planning Center for Integrated Education and Training in UPNVJT in Wonosalam". This textbook is a guide for students in planning a whole new housing environment. The compilation of textbooks on Housing Planning will make it easier for students to complete the task of planning a new housing environment. Besides that this textbook can also be used as a reference in architecture design course 6: designing residential facilities and preparing Final Projects related to the built environment, especially residential (residential) both horizontal and vertical housing.